Deep learning with python - Chollet, Francois (Shelter Island, NY : Manning Publications, 2021)
Deep Learning with Python, Second Edition introduces the field of deep learning using Python and the powerful Keras library. In this revised and expanded new edition, Keras creator François Chollet offers insights for both novice and experienced machine learning practitioners. As you move through this book, you ll build your understanding through intuitive explanations, crisp color illustrations, and clear examples. You ll quickly pick up the skills you need to start developing deep-learning applications.
1. What is deep learning? -- 2. The mathematical building blocks of neural networks -- 3. Introduction to Keras and TensorFlow -- 4. Getting started with neural networks: classification and regression -- 5. Fundamentals of machine learning -- 6. The universal workflow of machine learning -- 7. Working with Keras: a deep dive -- 8. Introduction to deep learning for computer vision -- 9. Advanced deep learning for computer vision -- 10. Deep learning for timeseries -- 11. Deep learning for text -- 12. Generative deep learning -- 13. Best practices for the real world -- 14. Conclusions -- Index.
Includes index.
Keywords: MACHINE LEARNING